Flow in New Zealand high-performance athletes and their intentions to use regulated breathing : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Auckland, New Zealand - Barrett, Jay Andrew (Massey University, 2018)
Flow, or being “in the zone” (Jackson & Csikszentmihalyi, 1999, p. 12), is associated with athletes’ best-perceived performance (Jackson, Thomas, Marsh, & Smethurst, 2001). Practising regulated breathing could be associated with experiencing flow; the current research sought to identify this potential relationship with New Zealand high-performance adult athletes. New Zealand high-performance adult athletes’ intentions to use regulated breathing in two behaviours (‘practising regulated breathing in a training routine’ or ‘using regulated breathing as a mental skills tool during competition’) along with the components of an individual’s intentions (instrumental and experiential attitudes, injunctive and descriptive norms and capacity and autonomy; Fishbein & Ajzen, 2010) were also researched. A cross-sectional survey was used to gather data. A t-test showed there was no statistically significant difference in the frequency flow was experienced between participants currently practising regulated breathing against those that were not, t(40) = 0.96, p = .342. Descriptive statistics and one-way ANOVAs showed the majority of the sample responded that they intended to practice regulated breathing in a training routine (64%) and use regulated breathing as a mental skills tool during competition in the future (76%) with no significant difference across the competition level competing at, F(2,87) = 0.26, p = .774 and F(2,87) = 0.56, p = .575, respectively. Finally, multiple linear regression models showed instrumental attitudes were the only significant predictor of intentions to perform regulated breathing in a training routine (Beta = .68, p < .001) or during competition as a mental skills tool (Beta = .82, p < .001). Participants’ components (instrumental and experiential attitudes, injunctive and descriptive norms and capacity and autonomy) estimated 67% of the variation in their intentions to practice regulated breathing in a training routine and 70% of the variation in their intentions to use regulated breathing as a mental skills tool during competition. Further evidence is needed to confirm the relationship between practising regulated breathing and how frequently flow is experienced. However, regulated breathing interventions could be appealing to New Zealand high-performance athletes.
Keywords: Athletes; Psychology; Sports; Psychological aspects; Breathing exercises; Performance